Customer orientation and office space performance: assessing the moderating effect of building grade using PLS-MGA - Cheah, Jun-Hwa; Ng, Siew-Imm; Ting, Hiram; Memon, Mumtaz Ali; Loo, Siat Ching Stephanie (International Journal of Strategic Property Management, 2019)
This study presents a framework to measure and empirically validate the relationship between customer orientation and office space performance. The framework uses two types of customer orientation (i.e., responsive customer orientation and proactive customer orientation) and two types of office space performance metrics (i.e., tenant satisfaction and tenant loyalty). Moreover, the building grade (Grade A and Non-grade A) is incorporated into the framework to assess its moderating effect on the relationships. 380 usable responses were collected from building managers in Grade A and Non-grade A buildings using a questionnaire survey. Partial least squares structural equation modeling was utilized to perform latent variable and multi-group analyses. The findings indicate that proactive customer orientation enhances satisfaction to a level not reached by responsive customer orientation as well as suggesting the applicability of both customer orientations in different scenarios. While proactive customer orientation practices lead to higher satisfaction in Non-grade A office ten-ants, responsive customer orientation practices lead to greater satisfaction in grade A office tenants. The latter tend to be more satisfied with Grade A office and thus loyal. Theoretical and managerial implications are discussed.